1966
DOI: 10.1099/00221287-43-3-383
|View full text |Cite
|
Sign up to set email alerts
|

The Survival of Escherichia coli sprayed into Air and into Nitrogen from Distilled Water and from Solutions of Protecting Agents, as a Function of Relative Humidity

Abstract: SUMMARYThe survival in air as a function of relative humidity (RH) and aerosol age is reported for Escherichia coli (strains B and Jepp) and for Serratia marcescens (strain U K 8 ) sprayed from suspensions in distilled water and in solutions of dextran and of raffinose. The survival in nitrogen ( > 99.9 yo) of E . coli (strains B, Jepp and commune) is given as a function of RH, when sprayed from suspension in distilled water and in raffinose solution. The results show that E . coli in the aerosol was subject t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
1

Year Published

1967
1967
2011
2011

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 24 publications
13
103
1
Order By: Relevance
“…Oxygen is known to be toxic to many bacterial aerosols, but often the effect may only be apparent at low r.h. (Hess, 1965;Cox, 1966;Benbough, 1967Benbough, , 1969Webb, 1967); it is possible that the poorer survival of L. pneumophila in drier air may be due in part to oxygen toxicity. One disadvantage of assessing microbial aerosol stability at only three representative r.h. values is that for many bacteria zones of relative instability exist at certain r.h. values (Anderson, 1966;Benbough, 1967;Cox, 1966Cox, , 1969Cox, , 1971) and similar zones of instability have been found for freeze-dried bacteria (Bateman et al 1961;Dewald et al 1967). The survey of the viability of L. pneumophila 74/81 aerosols held for 15 min showed that this organism survives poorly at 55 % r.h. compared with its stability at r.h. values slightly above and below this (65 and 40 % respectively); this suggests that such zones of instability also exist for legionella.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen is known to be toxic to many bacterial aerosols, but often the effect may only be apparent at low r.h. (Hess, 1965;Cox, 1966;Benbough, 1967Benbough, , 1969Webb, 1967); it is possible that the poorer survival of L. pneumophila in drier air may be due in part to oxygen toxicity. One disadvantage of assessing microbial aerosol stability at only three representative r.h. values is that for many bacteria zones of relative instability exist at certain r.h. values (Anderson, 1966;Benbough, 1967;Cox, 1966Cox, , 1969Cox, , 1971) and similar zones of instability have been found for freeze-dried bacteria (Bateman et al 1961;Dewald et al 1967). The survey of the viability of L. pneumophila 74/81 aerosols held for 15 min showed that this organism survives poorly at 55 % r.h. compared with its stability at r.h. values slightly above and below this (65 and 40 % respectively); this suggests that such zones of instability also exist for legionella.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were recovered from aerosols for 1 min, using raised impingers with a flow rate of 10-5 1/min (May & Harper, 1957). Impingers contained 10 ml of one of the following sterile fluids; distilled water, Page's saline (Page, 1967), PBMA (Cox, 1966) or GPMA (gelatine, 0-2 % w/v in PBMA).…”
Section: Organismsmentioning
confidence: 99%
“…Amongst these was the nature of the atmosphere, in that at low relative humidity (RH), but not at high RH, survival was much greater in nitrogen than in air (Cox, 1966a;Cox & Baldwin, 1966). The previous suggestion that this survival difference was owing to the toxic action of oxygen (Cox, 1966a) is now examined.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used were as previously reported (Cox, 1966a) except that in all experiments a rotating dnm container (Goldberg, Watkins, Boerk & Chatigny, 1958) was used for storing the aerosol cloud, and only Escherichia coli B sprayed from distilled water was studied. The drum apparatus used for the present work was similar to that used by Cox (1966a).…”
Section: Methodsmentioning
confidence: 99%
“…niger have been used extensively as a biological tracer (Harper & Morton, 1952;Harper et al 1958;Anderson, 1966;Cox, 1966;Benbough, 1969;Hambleton, 1970), but there is evidence that a proportion of the spores may die in the aerosol (Harper et al 1958;Anderson, 1966;Cox, 1966 B) and results with populations of small bacteria with long generation times (e.g. Pasteurella tularensis, live vaccine strain) are unreliable.…”
Section: Introductionmentioning
confidence: 99%